Digital Pemasaran dan Inovasi Desain Sebagai Faktor Yang Menentukan Daya Saing UMKM Batik Kulon Progo - Sugiyamin; Teguh Erawati; Deddy Setyawan; Nugroho Heri Cahyono (JCSE: Journal of Community Service and Empowerment, 2025)
This study examines the influence of digital marketing and design innovation on the competitiveness of batik MSMEs in Kulon Progo Regency. Challenges faced by MSMEs include a lack of design innovation, suboptimal use of digital marketing, low productivity of local wisdom-based motifs, and inadequate management of intellectual property rights. The study used a participatory approach involving material delivery, discussions, case studies, and financial simulations. The results indicate that the training successfully improved MSMEs' capabilities in social media management, live selling, and website creation. Design innovation also developed with the emergence of new motifs, the development of contemporary batik techniques, and improved IPR management. However, obstacles remain, such as an ineffective design team and incompletely integrated digital marketing. Recommendations for this study include strengthening the design team, optimizing digital strategies, utilizing AI-based design technology, and long-term follow-up research.